Assessing sustainability in environmental management: a case study in malaysia industry - Faiz, Mohd Turan; Kartina, Johan; Wan Nurul Syahirah, Wan Lanang (IOP Conf. Series: Materials Science and Engineering, 2017)
The scarcity in measuring the sustainability accomplishment has been restrained most of the companies in Malaysian industry. Currently, there are variety types of the measurement tools of the sustainability assessment that have been implemented. However, there are still not achieving the inclusive elements required by the worldwide claim. In fact, the contribution to the sustainability performance are only highlighted on the nature, financial along with society components. In addition, some of the companies are conducting their sustainability implementation individually. By means, this process approaching type is needed to be integrated into a systematic system approach. This paper is focussing on investigating the present sustainability tools in the environmental management system for Malaysian industry prior to the quantification of the sustainability parameters. Hence, the parameters of the sustainability have been evaluated then in order to accomplish this project. By reviewing on the methodology of this research it comprises of three phases where it starts with the analyzation of the parameters in environmental management system according to the Malaysian context of industry. Moving on to the next step is the quantification of the criterion and finally the normalisation process will be done to determine the results of this research either it is succeeded or vice versa. As a result, this research has come to the conclusion where the level of the sustainability compliance does not achieve the standard level of the targeted objectives though it has already surpassed the average level of the sustainability performance. In future, the understanding towards the sustainability assessment is acquired to be aligned unitedly in order to integrated the process approach into the systematic approach. Apart, this research will be able to help to provide a measurable framework yet finally bestowing the Malaysian industry with a continuous improvement roadmap in achieving excellence in environmental management system.